Probing the chiral magnetic wave with charge-dependent flow measurements in Pb-Pb collisions at the LHC - The ALICE collaboration; S. Acharya; D. Adamová; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (Journal of High Energy Physics, 2023)
Abstract The Chiral Magnetic Wave (CMW) phenomenon is essential to provide insights into the strong interaction in QCD, the properties of the quark-gluon plasma, and the topological characteristics of the early universe, offering a deeper understanding of fundamental physics in high-energy collisions. Measurements of the charge-dependent anisotropic flow coefficients are studied in Pb-Pb collisions at center-of-mass energy per nucleon-nucleon collision s NN $$ \sqrt{s_{NN}} $$ = 5.02 TeV to probe the CMW. In particular, the slope of the normalized difference in elliptic (v 2) and triangular (v 3) flow coefficients of positively and negatively charged particles as a function of their event-wise normalized number difference, is reported for inclusive and identified particles. The slope r 3 Norm $$ {r}_3^{Norm} $$ is found to be larger than zero and to have a magnitude similar to r 2 Norm $$ {r}_2^{Norm} $$ , thus pointing to a large background contribution for these measurements. Furthermore, r 2 Norm $$ {r}_2^{Norm} $$ can be described by a blast wave model calculation that incorporates local charge conservation. In addition, using the event shape engineering technique yields a fraction of CMW (f CMW) contribution to this measurement which is compatible with zero. This measurement provides the very first upper limit for f CMW, and in the 10–60% centrality interval it is found to be 26% (38%) at 95% (99.7%) confidence level.